The school of talents in the competencies society - Capobianco, Rosaria (Formazione & insegnamento, 2018)
This essay focuses its attention on the topic of talent’s enhancement in the school by referring to the student in his entirety and uniqueness. It’s very important for school to overcome standardized models of talent certification to offer the opportunity for each student to discover and enhance their personal attitudes through a personalized teaching. Today in the competencies society we could run the risk of thinking of a type of training that is too specialized, rigid and only oriented to work, whose its main focus is competence, instead the pedagogy of talents, prevent this risk, inviting the subject in his entirety and relational networks to focus on the logic of competences, without never losing sight of the different social spheres in which he is inserted.